Role of Alkaloidal Precipitants for the Assay of Aripiprazole Hydrochloride in Bulk and Pharmaceutical Formulations - Mohan Krishna, L.; Jayachandra Reddy, P.; Prasada Rao, K.V.S. (Asian Journal of Chemistry, 2011)
Simple spectrophotometric methods (A-C) for the assay of aripiprazole (APZ) based on the formation of its complex with alkaloidal precipitants are described. Aripiprazole under quantitative precipitation in the form of molecular complexes with iodine (method A), ammonium molybdate (method B) or phosphomolybdic acid (method C) when used in excess. In addition to precipitation reactions, colour reactions have also been combined to estimate aripiprazole. They are based on the colour formation with either unreacted precipitant of the filtrate (I2) or released precipitant from the molecular complex (method B or C) with chromogenic reagent such as P-N-methyl amino phenol sulphate-sulphanilic acid (method A), potassium thiocyanate (method B), cobalt nitrate Co(II)-disodium salt of ethylene diamine tetra acetic acid complex (method C).